Determination of Margin and Profit-Sharing Ratio in Maintaining Profitability of Islamic Banks - Yuliana; Sukmawati; Ayu Ariska (Institut Agama Islam Persis Bandung, 2024)
This study aims to analyze the determination of margin and profit-sharing ratio (nisbah) in maintaining the profitability of Islamic banks. Margin and nisbah represent two primary instruments in Islamic banking operational systems utilized to generate profits without violating Sharia principles. This study employs a qualitative method using a systematic literature review and descriptive analysis approach. Data was obtained from various relevant literature sources, including books, accredited journals, scientific articles, and official reports from financial authorities such as the Financial Services Authority (OJK). The analysis technique was conducted by examining and comparing related theories to obtain a systematic understanding of the relationship between margin determination, nisbah, and Islamic bank profitability. The results of murabahah indicate that margin determination in murabahah financing products must consider operational costs, financing risks, and market conditions, whereas the determination of the profit-sharing ratio must be based on principles of justice, transparency, and mutual agreement between the bank and customers. The balance between margin and nisbah is crucial for maintaining competitiveness while enhancing customer trust. Furthermore, this study reveals that financing continues to dominate the revenue structure of Islamic banks in Indonesia, which poses implications for the fundamental spirit of profit and loss sharing in Islamic banking. This study is limited to a literature review approach without empirical quantitative analysis. Future research is recommended to conduct empirical studies examining the direct impact of margin and nisbah determination policies on Islamic bank profitability using quantitative methods. The findings provide strategic guidance for Islamic bank management in designing optimal portfolio compositions between margin-based and profit-sharing-based financing to achieve sustainable profitability while remaining compliant with Sharia principles